Acute appendicitis related to Enterobius vermicularis infestation in a geriatric patient: a case report and literature review - Domingues, Joana C.; F. Mineiro, José (International Surgery Journal, 2025)
Acute appendicitis (AA) is a common surgical emergency with a multifactorial aetiology, rarely associated with intestinal parasites. This report highlights the case of a 93-year-old female who developed AA in association with Enterobius vermicularis (EV), a rare finding in this age group. The patient underwent successful laparoscopic appendectomy followed by antiparasitic therapy, with a favourable outcome. Parasitosis may mimic typical AA or represent a coincidental finding. This case emphasizes the importance of considering parasitosis in the differential diagnosis of AA, especially in atypical presentations or when contemplating non-surgical management. Laparoscopic appendectomy with antiparasitic treatment remains the standard of care.